A Modified Approach for Single-Port Laparoscopic Repair of Inguinal Hernias in Children - Fazeli, Ali (Adv Biomed Res, 2020)
BACKGROUND: Although traditional open groin incision repair has been used routinely for decades, the benefit of the minimally invasive surgery has challenged the traditional open method. Nowadays, laparoscopic herniorraphy has evolved to making it more minimally invasive from 3 to 2 and now single port and from intracorporeal to extracorporeal knotting. This study aimed to evaluate a new modification of single port laparoscopic herniorraphy in children with congenital inguinal hernia. MATERIALS AND METHODS: In this single-institution randomized case–control study 190 children who suffered from congenital inguinal hernia were divided into two groups randomly: Group 1 (N = 73) undergone a single-port modified extracorporeal purse-string sutures (laparoscopic surgery [LS]) and Group 2 (N = 117) undergone open surgery (OS). RESULTS: The mean age of the patients at operation time was 28.79 ± 11.45 months. Overall, three patients (1.57%) had intraoperative retroperitoneal hemorrhage. The duration of anesthesia and operation for those undergoing bilateral operation were significantly shorter in LS group. There was no statistically significant difference in individual postoperative complication rates between the groups. The proportion of overall post-operative complications was 4 (5.4%) in LS and 13 (11.1%) in OS group (P = 0.18). Proportion of trapped cryptorchidism was significantly higher in the OS group. CONCLUSION: In conclusion for children with inguinal hernia, we had found the benefits of single-port modified extracorporeal purse-string for reduction the operative time, trapped testes and better cosmetics and parents' satisfaction.